2012
DOI: 10.3390/medicina48020016
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Gold Nanoparticles in the Treatment of Established Collagen Arthritis in Rats

Abstract: Background and objective. The role of gold nanoparticles (AuNPs) in the treatment of autoimmune diseases remains vague. Therefore, the aim of this study was to determine the effect of AuNPs in the treatment of rats with established collagen-induced arthritis (CIA). Material and Methods. A total of 24 Wistar male rats with established CIA were used. AuNPs measuring 13-nm and 50-nm were prepared according to standard procedures, and their size was determined using transmission electron microscopy. These gold par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
37
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(40 citation statements)
references
References 25 publications
2
37
0
1
Order By: Relevance
“…Support for this conclusion may be found in the only other study available for comparison, which demonstrated that a positive in vivo treatment effect of AuNPs was also not dependent on particle size 11 . Interestingly, next to other dramatic positive effects of AuNPs in this study, a reduction in cell necrosis was also reported, further validating our observation of reduced LDH activity.…”
Section: Discussionsupporting
confidence: 89%
“…Support for this conclusion may be found in the only other study available for comparison, which demonstrated that a positive in vivo treatment effect of AuNPs was also not dependent on particle size 11 . Interestingly, next to other dramatic positive effects of AuNPs in this study, a reduction in cell necrosis was also reported, further validating our observation of reduced LDH activity.…”
Section: Discussionsupporting
confidence: 89%
“…GNP were recently proposed as a new treatment for arthritis and other rheumatic diseases due to their anti‐inflammatory properties . Pereira et al.…”
Section: Gold Nanoparticles For Ophthalmic Therapymentioning
confidence: 99%
“…This was accompanied with 0.25 mL of 20 nm gold nanoparticles (Ted Pella, Redding, CA, USA) at a concentration of 7.0 × 10 11 . The 20 nm AuNPs were utilized due to a previous study demonstrating the efficacy of nanoparticles in this size range in reducing inflammation [28]. Nanoparticles were functionalized with amine groups by the addition of 0.001 mg/mL 2-mercaptoethyamine (Cysteamine) (Sigma-Aldrich, St. Louis, MO, USA) to the nanoparticles.…”
Section: Genipin Gold Nanoparticles and The Crosslinking Proceduresmentioning
confidence: 99%